(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article the moral values of kazakh culture are exposed to the kul’turologicheskomu analysis, their meaningfulness is shown for the show of ethnic making transit society, the human measurings of ethics values are selected. Keywords: value, tradition, innovations, morality, humaneness, national, education, ritual.